Extraction and Characterization of Collagen from Sand Sea Cucumber (Holothuria scabra) - Syahputra, Gita; Hariyatun, Hariyatun; Firdaus, Muhammad; Santoso, Pugoh (Jurnal Ilmu Pertanian Indonesia, 2021)
Sand sea cucumber (Holothuria scabra) is an aquatic product that belongs to Echinodermata, a habitant in almost all Indonesian seas. The main component of the sea cucumber is protein, one of which is collagen. This study aimed to extract and characterize collagen from the species using the acid-base extraction method. The characterization of sea cucumber collagen includes molecular weight, amino acid components, Fourier transform infrared spectrophotometry, and scanning electron microscopy analysis. This study has successfully extracted collagen from the sample using an extraction system: NaOH 0.1 M; CH3COOH 0.1 M; and distilled water under 45°C treatments, gave 6% yield. The collagen has a molecular weight 110-130 kDa. Based on the infrared spectra, the specific functional groups of the collagen are amide A (3379.29 cm-1), amide B (2924.09 cm-1), amide I (1681.93 cm-1), amide II (1560.41 cm-1), and amide III (1249.87 cm-1). The collagen falls into type I. We suggest an alternative resource of collagen from sand sea cucumber, other than poultry and mammals. Keywords: characterization, collagen, extraction, fishery, sand sea cucumber